2007
DOI: 10.1016/j.addbeh.2007.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Work stress and alcohol use: Examining the tension-reduction model as a function of worker's parent's alcohol use

Abstract: In an effort to identify groups who may be more vulnerable to tension-reduction drinking (Frone, 2003), we examine whether drinking alcohol in response to work stress varies as a function of whether workers were raised in homes where (a) both parents abstained from alcohol, (b) at least one parent drank nonproblematically, (c) at least one parent drank problematically, or (d) both parents drank problematically. Employees participating in a large, longitudinal study who reported using alcohol in the previous ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
(9 reference statements)
0
11
0
3
Order By: Relevance
“…Previous research concluded that work-related stress is associated and increase an individual's vulnerability to burnout, job satisfaction and physical as well as mental health outcomes (Piko, 2006;Pillay, 2009). Other health problems related to the effects of work stress include: cardiovascular disorders (Li, Loerbroks, Bosma, & Angerer, 2016), gastrointestinal disorders (Huerta-Franco, 2013), musculoskeletal disorders (Nafeesa, Vidhya, Vijayalakshmi, & Rajkumar, 2017), anxiety and depression (Fan, Blumenthal, Watkins, & Sherwood, 2015), work fatigue (Rose et al, 2017), insomnia (Deguchi et al, 2017), alcohol abuse (Moore, Sikora, Grunberg, & Greenberg, 2007), decrease marital quality (Obradović & Čudina-Obradović, 2013) and disruption of social interaction (La Torre et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research concluded that work-related stress is associated and increase an individual's vulnerability to burnout, job satisfaction and physical as well as mental health outcomes (Piko, 2006;Pillay, 2009). Other health problems related to the effects of work stress include: cardiovascular disorders (Li, Loerbroks, Bosma, & Angerer, 2016), gastrointestinal disorders (Huerta-Franco, 2013), musculoskeletal disorders (Nafeesa, Vidhya, Vijayalakshmi, & Rajkumar, 2017), anxiety and depression (Fan, Blumenthal, Watkins, & Sherwood, 2015), work fatigue (Rose et al, 2017), insomnia (Deguchi et al, 2017), alcohol abuse (Moore, Sikora, Grunberg, & Greenberg, 2007), decrease marital quality (Obradović & Čudina-Obradović, 2013) and disruption of social interaction (La Torre et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…So while there is evidence from animal, preclinical and clinical studies that stress leads to overeating and excessive drinking to self-medicate (Sinha, 2007), research on stress suggests substantial heterogeneity. To date, differences in response to stress have been explained by such factors as coping style, genetic proclivity, and other aspects of family history (Moore, Sikora, Grunberg, and Greenberg 2007). Secondly, income and substitution effects may also contribute to the ambiguity of earlier findings.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also shown that work-related stress is related to harmful or problematic levels of alcohol use among vulnerable employees. 40,41 The extent to which these findings relate to employed parents is unclear. Further research is needed to determine how employment and work-related stress may contribute to alcohol use among parents.…”
mentioning
confidence: 99%